UPACARA ADAT PERKAWINAN BENGKULU (Analisis Filosofis, Nilai Islam dan Kearifan Lokal) - Samsudin Samsudin (Universitas Islam Negeri Fatmawati Sukarno, 2018)
The philosophical values contained in the building of the traditional marriage of the Malay community of the City of Bengkulu are a reflection of the socio-cultural relations of Malayness with Islamic values. Historically, Beng- kulu Malay Islam was an incarnation of acculturation and assimilation between Muslims who came to Bengkulu. The position of the process of acculturation of Islam in Bengkulu Malay society, became very significant as the basis of the cultural process of Bengkulu society until now. Acculturation of values and internalization of Islamic values is very func- tional in shaping philosophical values in the custom of marriage of the Bengkulu community. This is expressed in every stage of the traditional marriage, there are ritual processions that are inter-related with local wisdom, Islamic values and other Islamic philosophical meanings.